‘You want to chill with the big boys’: Proverbs 21:4–7 and drug trafficking in Nigeria - Uroko, Favour C.; Nnadi, Success A. (Verbum et ecclesia, 2022)
Although progress has been made in the study of Proverbs 21:4–7, existing literature is yet to shift focus on the relevance of the pericope in examining the different aspects of drug trafficking by Nigerians. There is no month that passes without the news of a Nigerian caught in a national or international airport for one form of drug trafficking or another by the National Drug Law Enforcement Agency (NDLEA). These drugs include cocaine, tramadol and Indian hemp, among others. This has brought disgrace to those caught in the act, their families as well as Nigerian society. Those who were supposed to protect and fight against these drug traffickers have also involved themselves, as pastors and policemen have also been caught trafficking drugs. Proverbs 21:4–7 is a storehouse of moral instruction and has always been regarded as containing the concentrated deposit of ancient Israelite morality. It was written to sharpen an individual’s ability not to be crafty or cunning but to transform a person of evil devices into a person of discretion, turning craftiness into prudence. This study used literary analysis as its research method. There is a close relationship between Proverbs 21:4–7 and the activities of drug traffickers in Nigeria. The themes embedded in the pericope, such as contentment, righteousness, diligence, self-control and patience, are believed to speak anew to the increasing activities of drug traffickers in Nigeria.Intradisciplinary and/or interdisciplinary implicationsDrug trafficking by Nigerians, nationally and internationally, has increased social crimes and Proverbs 21:4–7 provides new approach for solving this anomaly.